EFEK ANTI-INFLAMASI INFUSA HERBA KUMIS KUCING (Orthosiphon spicatus B.B.S.) KONSENTRASI 5%, 10%, DAN 20% - Metha Anung Anindhita (LPPM Universitas Pekalongan, 2014)
Orthosiphon spicatus B.B.S. traditionally used as anti-inflammatory. This study was aimed to find out anti-inflammatory effect of Orthosiphon spicatus B.B.S. herb infusa in white male rats. The rats were randomly devided into 5 groups. A negative control group treated with distilled water. A positive control group treated with Na diclofenac. The third group treated with Orthosiphon spicatus B.B.S. herb infusa 5%. The fourth group treated with Orthosiphon spicatus B.B.S. herb infusa 10%, and the fifth group treated with Orthosiphon spicatus B.B.S. herb infusa 20%. The edema volume was measured starting early after treatment was given every half hour for six hours. Area under curve (AUC) values were analyzed by one way ANOVA and LSD test. The data result indicate Orthosiphon spicatus B.B.S. in different concentrations significantly different to the negative control. It can be conclude that Orthosiphon spicatus B.B.S. herb infusa have anti-inflammatory effects.